Некоторые физико-химические свойства ДНК вируса денсонуклеоза комаров - Бучацкий, Л.П.; Филенко, О.М. (Биополимеры и клетка, 1988)
Изучены некоторые физико-химические свойства ДНК ВДК: взаимодействие с формальдегидом, температура плавления, плавучая плотность в хлористом цезии, коэффициент седиментации. Показано, что по ряду свойств ДНК ВДК близка к представителям рода парвовирусов. Вивчено деякі фізико-хімічні властивості ДНК ВДК: взаємодія з формальдегідом, температура плавлення, плавуча щільність у хлористому цезії, коефіцієнт седиментації. Показано, що за низкою властивостей ДНК ВДК близька до представників роду парвовірусів. Mosquito densonucleosis virus (MDV) is isolated from the blood-suckling mosquito Aedes aegypti and properties of its DNA are characterized. The reaction of formaldehyde with MDV virion and extracted DNA suggests that DNA in situ and in vitro is single-stranded. DNA extracted from MDV has a buoyant density of 1.734 g/cm³ in cesium chloride. The S₂₀, was determined in alcaline sucrose gradients to be 9.2, that corresponds to the molecular weight 2.5X10⁶ daltons. Basing on the melting curve and the reaction with formaldehyde the DNA of MDV is believed to be closely related to members' of the parvovirus subgroup.